(untitled) (Journal of Rangpur Medical College, 2024)
Background: Diabetes mellitus presents a prevalent endocrine and metabolic challenge globally. Type-2 diabetic patients exhibit a heightened incidence of dyslipidemia, characterized by elevated low-density lipoprotein (LDL), diminished high-density lipoprotein (HDL), or increased triglycerides (TG) levels. This phenomenon poses a significant public health concern both internationally and within our nation. Objective: This study aimed to assess the patterns of dyslipidemia among diabetes patients. Methods: This cross-sectional observational study was conducted at the Outpatient Department (OPD) of Shaheed Ziaur Rahman Medical College Hospital, Bogura, from July 2018 to June 2019. Both male and female patients with Type2 diabetes were considered as the study population. A total of 90 patients were selected as study subjects through purposive sampling.The study included 45 diabetic patients on therapy, divided into male (A1, n=19) and female (A2, n=26) subgroups. Additionally, 45 newly diagnosed diabetic patients were categorized into male (B1, n=15) and female (B2, n=30) subgroups.Analysis was performed by using SPSS (Statistical Package for Social Science) version 22.0. Results: The study found similar ages and BMI among groups. Elevated serum TC was noted in 31.6%, 19.2%, 26.7%, and 30% of subjects in A1, A2, B1, and B2 respectively. High serum TG levels were observed in 36.8%, 38.5%, 40%, and 66.7% of subjects in the respective groups. Dyslipidemia prevalence varied, with A1 at 57.9%, A2 at 53.8%, B1 at 46.7%, and B2 at 76.7%. High HbA1C was prevalent in B1 and B2 (100%). Conclusion: Dyslipidemia patterns among diabetes patients exhibit significant variability, with elevated serum total cholesterol, triglycerides, and low-density lipoprotein levels, alongside reduced high-density lipoprotein levels, commonly observed. These findings underscore the importance of tailored lipid management strategies in mitigating cardiovascular risk in this high-risk population. J Rang Med Col. September 2024; Vol. 9, No. 2: 78-83